On the rediscovery of Schneider's Pitta in Sumatra - Phil Hurrell (KUKILA, 1989)
Schneider's Pitta Pitta schneideri is endemic to the montane rain forest of Sumatra and may be confined to isolated peaks of the Barisan Range in West Sumatra. There have been no records for over 70 years. This paper reports the discovery of a pair of Schneider's Pitta in Kerinci-Seblat National Park and suggests that further study of their range, status and biology is urgently needed.